Profile of Online Information Service Program Implementation at SMPN in Padang Pariaman District - Mardhiyani, Sufni; Solina, Wira; Chandra, Yasrial (Lembaga Riset Mutiara Akbar, 2022)
This research is motivated by the obstacles of BK teachers in providing questionnaires to analyze the needs of students through WhatsAPP Group, students who do not respond and are indifferent in the implementation of the information services provided and the obstacles of BK teachers in determining information service materials to be provided through WhatsAPP Group . The purpose of this study is to describe 1). Planning, 2). Implementation, 3). Evaluation, 4). Result analysis 5). Follow-up in the implementation of online guidance and counseling teacher information services. This research was conducted using a quantitative descriptive method. The research population was 49 BK teachers who were selected by purposive sampling technique as many as 30 BK teachers samples. The instrument used is a questionnaire. Meanwhile, for data analysis using descriptive statistics with percentage techniques. The results of research on the implementation of online information service programs at SMPNs throughout Padang Pariaman Regency are seen from 1). Planning is in the effective category, 2). Implementation is in the effective category, 3). Evaluation is in the effective category, 4). The analysis of the results is in the effective category, 5). Follow-up is in the effective category. Based on the results of this study, it is recommended for BK teachers to further improve the implementation of online information services in order to get even better results.